2018
DOI: 10.1002/csr.1518
|View full text |Cite
|
Sign up to set email alerts
|

Does sustainability marketing strategy achieve payback profits? A signaling theory perspective

Abstract: Despite the importance of sustainability marketing strategy, its influence on firm performance is still inconclusive. In this study, we explore how and under what conditions sustainability marketing strategy influences firm performance by including the customer as an external stakeholder. Drawing on signaling theory, we test the hypothesized relationships using survey data collected from 264 Chinese firms. The results reveal that customer loyalty partially mediates the relationship between sustainability marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 58 publications
1
47
0
3
Order By: Relevance
“…Energy shortage, environmental pollution, and customers' growing awareness of environment-friendly products are driving firms to concern for environmental management (Taoketao, Feng, Song, & Nie, 2018;Wang, Feng, Zhao, & Song, 2018). These pressures subsequently turn into a momentum for firms to engage in green innovation (Du et al, 2018).…”
Section: Definitions: Green Innovation and Green Supply Chain Learningmentioning
confidence: 99%
“…Energy shortage, environmental pollution, and customers' growing awareness of environment-friendly products are driving firms to concern for environmental management (Taoketao, Feng, Song, & Nie, 2018;Wang, Feng, Zhao, & Song, 2018). These pressures subsequently turn into a momentum for firms to engage in green innovation (Du et al, 2018).…”
Section: Definitions: Green Innovation and Green Supply Chain Learningmentioning
confidence: 99%
“…External involvement helps firms to gain resources and capabilities externally to meet customer demand (Jayaram, ; Mishra & Shah, ; Wu, ). It is generally acknowledged that involving external stakeholders is critical in achieving competitive advantages and performance (Dögl & Behnam, ; Feng, Sun, & Zhang, ; Singh & Power, ; Taoketao, Feng, Song, & Nie, ). From the perspective of supply chain management, we define external involvement as the degree to which customers and suppliers are involved in a firm's green product innovation programs.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting green innovation to reduce the negative influences on natural environment has been deemed as an important source of competitive advantage (Dangelico, Pujari, & Pontrandolfo, ; Gerstlberger, Præst Knudsen, & Stampe, ; Huang & Li, ). Existing literature suggested that both the institutional and market pressures have forced firms to attempt to implement green innovation (Chen, Yi, Zhang, & Li, ; Lee, Kim, & Kim, ; Taoketao, Feng, Song, & Nie, ). Although much of the previous research has focused on the performance consequences of green innovation (e.g., Huang & Li, ; Tang, Walsh, Lerner, Fitza, & Li, ), how green innovation performance is influenced by green customer and supplier integration is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting green innovation to reduce the negative influences on natural environment has been deemed as an important source of competitive advantage (Dangelico, Pujari, & Pontrandolfo, 2017;Gerstlberger, Praest Knudsen, & Stampe, 2014;Huang & Li, 2017). Existing literature suggested that both the institutional and market pressures have forced firms to attempt to implement green innovation (Chen, Yi, Zhang, & Li, 2018;Lee, Kim, & Kim, 2018;Taoketao, Feng, Song, & Nie, 2018).…”
Section: Introductionmentioning
confidence: 99%